Diagnostic Accuracy of Gold Standar and PH Sensor Prototype for Cancer Patient - Adhisty, Karolin; Maulida, Mutia Nadra; Yeni, Yeni (GLOBAL HEALTH SCIENCE GROUP, 2024)
Diagnosis is an integral part of quality health care in the nursing care process. Enforcement of the diagnosis can be optimal if accompanied by supporting objective data. Cases of nausea and vomiting that occur as a result of the effects of chemotherapy can certainly be minimized if the value of stomach acid is known, which is the objective data for these patients. This prototype is useful for assisting diagnosis in assessing the pH of stomach acid that occurs. Objective: The purpose of this study is to find a correlation value that can compare and assess the error score of the prototype being developed. Method: Research and development used in this study aims to determine the comparison of product values with the standard tools used. Sample consists of 55 selected reagents with pH results that will be compared between standard pH tools and prototype. Data analysis uses an accuracy formula based on the formulation Results: The data accuracy value was 99.87% and the data analysis used Mann Whitney with a value of> 0.05, stating that there was no difference in the score obtained from the prototype and the standard tools used Conclusions: These results indicate that the prototype with accurate values can be used to help obtain the pH value of stomach acid in cancer patients so that treatment can be given optimally.